A prospective randomised study comparing intermittent intramuscular regimen and intravenous infusion regimen of magnesium sulfate in the treatment of severe preclampsia and eclampsia - Dwivedi, Joshita; Chakrabarti, Shekhar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Eclampsia and preeclampsia are important causes of mortality during childbirth and puerperium. Commonly used regimens of magnesium sulfate are i.m. Pritchard regimen and i.v. zuspan regimen. This study was done with aim to compare the efficacy of i.m. regimen with i.v. regimen for prevention and recurrence of seizures. Methods: This study was carried out in the department of obstetrics and gynaecology, in a medical college in north India. 88 patients presenting with pre-eclampsia and eclampsia were included. Duration of the study was 18 months (from 1st October 2017-31st March 2019). The patients enrolled were classified randomly into two groups, group A and group B. Our target was to include 50 patients in both groups but few patients left against medical advice and not all patients met inclusion criteria group A was given the following regimen- loading dose of magnesium sulfate 4 gm MgSO4 in 12 ml normal saline slow intravenous infusion in 10-15 minutes and 5 gm MgSO4 deep intramuscular route each buttock, then maintenance dose of magnesium sulfate 5 gm alternate buttock group B was given- loading dose of magnesium sulfate 4 gm MgSO4 in 12 ml normal saline slow i.v. infusion in 10-15 minutes then maintainence dose of magnesium sulfate i.v infusion 1 gm/hr. Results: There was no significant difference between serum Mg2+ levels measure at 0 hours (baseline), 2 hours, 4 hours, 6 hours and 8 hours after administration of loading dose in both groups. Conclusions: The intermittent i.m. regimen and i.v. infusion regimen are comparable in terms of recurrence and prevention of seizure, maternal and neonatal outcome.